Development of Spiritual Mental After The Earthquake Tragedy - Rahmawati Rahmawati; Andi Reni (Simposium Antar Bangsa Seminar dan Workshop)
This writing object is to recognize how the development of spiritual mental of earthquake disaster victims that recently experienced Indonesian people in certain location. This is important thing because the disaster they experienced, caused many things like loss, traumatic suffer for them psychologically. There are categories of disasters that considered bring psychological effect towards disaster victims, they are namely disaster, non-nature disaster, and social disaster. Although situational of psychological effect towards mental after the disaster occurred and bring suffer to their heart physically or mentally. The victims are obviously feeling emptiness as they lost their family, job, as well as home. Psychologists for religion conclude that, there are many mental which possessed by victims. Those things caused by inner suffer which experienced by victims are correlate with religiousness. Those victims who have strong conviction towards religion value tend to relieve faster and easier to handle their inner suffer. As distinct from those who are strong, the victim with less conviction are tend to express their disappointment excessively and have strong trauma. In this writing, qualitative method used as approach. Technique of collecting data in this writing is observing through media, writing, and interview. The data will be collected and analyzed in this writing. As the result, the development of spiritual mental towards disaster victims is increasing. This can be seen from some activities of society in connecting their soul to god. From rarely pray changed to spiritual habit, as well as behave well to others. The other factors that can develop their mental they are namely; togetherness, geographic factor, educational factor either formal or non-formal as well as local wisdom.